Liability of Notaries and PPAT in the Making of Sales and Purchase Agreements of Land with Formal Defects: Study of Decision Number 309/PDT.G/2024/PN.MATARAM - Aida Musyarrifah Hasri Putri; Hirsanuddin Hirsanuddin; M.Yazid Fathoni (Warmadewa Press, 2026)
This study aims to analyze: (1) Regarding the basis of the judge's consideration in deciding the case in Decision Number 309/Pdt.G/2024/PN Mataram, whether the notary and the defendants in the control of the disputed object constitute an unlawful act. And (2) The responsibility of the notary or sanctions for the notary for making a land sale and purchase agreement that does not meet the legal validity requirements according to the law. This research is motivated by a land dispute jointly owned by two people, namely an uncle and a nephew, where one party, the nephew, then transferred the land by making a Preliminary Sale and Purchase Agreement (PPJB), followed by a power of attorney, and a Sale and Purchase Deed (AJB) without the knowledge of the other party. This led one party to file a lawsuit in court. The research method used is normative legal research with three approaches, namely the conceptual approach, the statutory approach, and the case approach. The sources of legal materials consist of primary, secondary, and tertiary legal materials, which are analyzed using qualitative analysis techniques. The results of the study indicate that in the judge's consideration, the judge partially approved the plaintiff's claim and stated that the deed that was made did not meet the requirements of a valid agreement. Furthermore, the judge also decided that regarding the consequences of the PPJB, Power of Attorney, AJB, and SHM in the name of the defendants, it was declared invalid. Therefore, the judge considers the actions of the defendants as unlawful acts under Article 1365 of the Civil Code. From the perspective of the liability of Notaries/PPAT and the legal consequences of the decision on the deeds made by the notary, if there is negligence, carelessness, or violation of statutory provisions causing losses during the performance of their duties, they can be held accountable civilly, administratively, or ethically.